Small scale farmers utilization and perceptions of Bambara groundnut production in South Africa: a case study in a semi-arid region of Limpopo - Cook, David (Department of Environmental and Geographical Science, 2018)
World food security will be one of the greatest global challenges in the 21st century and utilisation of an increased range of food crops is generally regarded as being vital to meeting this challenge, including the use of legumes. Bambara groundnut (Vigna subterranea) is an African indigenous legume that shows great potential to improve the food and economic security of small scale farmers living in semi-arid regions of South Africa. This study sought to investigate the potential for Bambara groundnut to enhance the food and economic security of small scale farmers in the Capricorn District of Limpopo Province, South Africa. A total of 43 Bambara groundnut producers were interviewed about Bambara groundnut production and their perceived enablers and barriers of utilizing Bambara groundnut. The study found that the majority of Bambara groundnut producers were old (>65 years of age), female small scale farmers who produced the crop for primarily household use. There were however a small number of farmers who produced Bambara groundnut on a larger scale, mostly to sell. Most farmers perceived that local demand was higher than supply and were able to obtain a high market value for Bambara groundnut. There appeared to be potential economic opportunities for many of the farmers to sell Bambara groundnut. The main reason why most farmers in this study did not sell Bambara groundnut was because the yields they obtained were too low. The main enablers perceived by farmers for Bambara groundnut production were a) The high nutritional value of Bambara groundnut; b) The good taste of the seeds; c) The nitrogen fixation properties of this legume and its ability to improve soil fertility; d) The legume intercrops well with maize; e) Bambara groundnuts high drought resistance; f) Cultural traditions associated with Bambara groundnut; and g) Use as animal feed. The main barriers were a) Low yielding characteristics of Bambara groundnut; b) Lack of available farmland; c) Lack of irrigation; d) Poor land management practices; e) Low soil fertility; and f) The crop's susceptibility to water logging. Overall the farmers were positive about Bambara groundnut production and could potentially benefit from advancements made in this sector of agriculture. The study concludes with recommendations to help improve small scale farmers' production of Bambara groundnut with the aim of improving their food and economic security.